2016
DOI: 10.1016/j.bpj.2015.11.2915
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Ligand Selectivity Across Bromodomain Families

Abstract: sampling (REUS) molecular dynamics simulations[2]. REUS is a powerful conformational sampling method to overcome energy barriers. We applied this method to the HDAC3-T247 system and HDAC2-T247 system. These have very similar amino-acid sequences and similar structures. From results of these simulations, we obtained free energy landscapes. The results of these calculations show that the docked state is the most stable in the HDAC3-T247 system but in the HDAC2-T247 system, the docked state is less stable than un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Recently, Aldeghi et al reported accurate absolute free energy calculations for a set of diverse inhibitors binding to bromodomain-containing protein 4 that is based on a thermodynamic cycle. 3 They achieved a mean absolute error of 0.6 kcal/mol −1 using X-ray structures and 1.0 kcal/mol using docked structures. However, the approach was also too computationally demanding for use in screening large numbers of candidate drugs.…”
Section: ■ Accurate Prediction Of Binding Energies Is Hard and Resour...mentioning
confidence: 95%
“…Recently, Aldeghi et al reported accurate absolute free energy calculations for a set of diverse inhibitors binding to bromodomain-containing protein 4 that is based on a thermodynamic cycle. 3 They achieved a mean absolute error of 0.6 kcal/mol −1 using X-ray structures and 1.0 kcal/mol using docked structures. However, the approach was also too computationally demanding for use in screening large numbers of candidate drugs.…”
Section: ■ Accurate Prediction Of Binding Energies Is Hard and Resour...mentioning
confidence: 95%
“…Molecular Mechanic/Poisson-Boltzmann Surface Area (MMPBSA) method was used to obtain the binding free energy of the interaction between ligandprotein complexes (Aldeghi et al, 2017). This employs ensembles derived from MD simulation.…”
Section: Mm/g/p/bsa Binding Free Energy Calculationsmentioning
confidence: 99%
“…For example, Aldeghi et al performed ABFE calculations on a set of 11 diverse bromodomain-containing protein 4 (BRD4) inhibitors that yielded an absolute error of 0.6 kcal/mol for a set of validation molecules and 1.0 kcal/mol for blinded predictions. 98 More recent work by Araujo et al presented a structure-based virtual screening protocol that culminates with ABFE calculations. 99 The authors found promising hits for ALK-5 inhibitors that were initially identified from docking, but further characterized with ABFE calculations to add confidence in the predictions, although these molecules have yet to be confirmed as ALK-5 inhibitors.…”
mentioning
confidence: 99%
“…Another advantage of ABFE calculations is the ability to compare predicted binding energies across different targets, because the binding energies computed are on an absolute scale. 98 This allows for in silico selectivity screening, where one could optimize narrow selectivity (binding to a single target and not undesirable off-targets) or broad promiscuity (multiple targets for polypharmacology or multiple protein variants to evade drug resistant mutations). While there are limited examples where this approach has been applied in the context of virtual screening, we foresee this as a high-value application area for ABFE in future vHTS campaigns.…”
mentioning
confidence: 99%